Risk Factors for Rebleeding after Emergency Endoscopic Treatment of Dieulafoy Lesion - Yongkang Lai; Jianfang Rong; Zhenhua Zhu; Wangdi Liao; Bimin Li; Yin Zhu; Youxiang Chen; Xu Shu (Canadian Journal of Gastroenterology and Hepatology)
Background and Objective: Dieulafoy lesion is a rare, but life-threatening, cause of gastrointestinal hemorrhage, and endoscopic therapy is the preferred first-line treatment. The present study aims to analyze the risk factors for rebleeding after endoscopic hemostasis of gastroduodenal Dieulafoy lesion. Methods. A retrospective review of patients with Dieulafoy lesion who developed acute gastrointestinal bleeding and were treated primarily with endoscopic therapy from September 2014 to April 2019 was conducted. Results. A total of 133 patients with Dieulafoy lesion were included in the present study. The mean age of these patients was 56.05 ± 16.58 years, and 115 patients were male. Among these 133 patients, 26 patients developed rebleeding within 30 days of endoscopic therapy. The 30-day rebleeding rate for pure injection therapy (epinephrine, cyanoacrylate, or lauromacrogol injection alone), nonpure injection therapy (argon plasma coagulation, band ligation, and hemoclip application alone), and combination therapy (combination of any >2 methods) was 45.2%, 12.8%, and 11%, respectively. In the univariable analysis, endoscopic treatment, prothrombin time, gender, Rockall score, and leukocyte count were the risk factors for rebleeding. In the multivariable analysis, pure injection endoscopic treatment, white blood cells (>10 × 109/L), and prothrombin time >12 seconds were the independent risk factors for rebleeding. Conclusion. Patients who undergo pure injection endoscopic treatment and have a high leukocyte count (>10 × 109/L) or elevated prothrombin time (>12 seconds) have an increased risk of rebleeding within 30 days after endoscopic treatment for gastroduodenal Dieulafoy lesion. Combined endoscopic treatment is the most effective therapy to prevent rebleeding in gastroduodenal Dieulafoy lesion.